Performance de guerrilha: poéticas-visuais negras como estratégia de autodefesa e enfrentamento ao racismo - Priscila Rezende Pinto (2024)
This research analyzes part of the notions of the emotion of anger and its presence in human relationships, correlating such notions with the experience of Black people in society. The objective is to understand the consequent occurrence of this emotion in the constitution of the corporeality of Black fellow which, transmuted into performative action, will enable the elaboration of art as a viable strategy of self-defense and confrontation against colonial violence and racism. To do this, we will investigate the performances Us agreed not to die by Jota Mombaça, A thousand liters of Black, by Lucimélia Romão, and my artistic works, such as Bombril, Bargain, Come... to be unhappy and Muchas gracias, pero no!. Based on the images and speeches that make up the works listed here, I draw a reflection on the identification and appropriation of the emotion of anger as the driving force and fuel of these poetic-visual and scenic creations.